Analysis of urinary cathepsin C for diagnosing Papillon–Lefèvre syndrome. (4th January 2016) - Hamon, Yveline; Legowska, Monika; Fergelot, Patricia; Dallet‐Choisy, Sandrine; Newell, Louise; Vanderlynden, Lise; Kord Valeshabad, Ali; Acrich, Karina; Kord, Hadi; Charalampos, Tsamakis; Morice‐Picard, Fanny; Surplice, Ian; et al.
Abstract : Papillon–Lefèvre syndrome (PLS) (OMIM: 245000) is a rare disease characterized by severe periodontitis and palmoplantar keratoderma. It is caused by mutations in both alleles of the cathepsin C (CatC) gene CTSC that completely abrogate the proteolytic activity of this cysteine proteinase. Most often, a genetic analysis to enable early and rapid diagnosis of PLS is unaffordable or unavailable. In this study, we tested the hypothesis that active CatC is constitutively excreted and can be easily traced in the urine of normal subjects. If this is true, determining its absence in the urine of patients would be an early, simple, reliable, low‐cost and easy diagnostic technique. All 75 urine samples from healthy control subjects (aged 3 months to 80 years) contained proteolytically active CatC and its proform, as revealed by kinetic analysis and immunochemical detection. Of the urine samples of 31 patients with a PLS phenotype, 29 contained neither proteolytically active CatC nor the CatC antigen, so that the PLS diagnosis was confirmed. CatC was detected in the urine of the other two patients, and genetic analysis revealed no loss‐of‐function mutation in CTSC, indicating that they suffer from a PLS‐like condition but not from PLS. Screening for the absence of urinary CatC activity soon after birth and early treatment before the onset of PLS manifestations will help to prevent aggressive periodontitis and loss of many teeth, and should considerably improve the quality of life of PLS patients. Abstract : Papillon‐Lefèvre syndrome (PLS) is caused by mutations in the cathepsin C (CatC) gene CTSC that block its protease activity. CatC can be immunologically and enzymatically detected in 100% of urine samples of healthy individuals but none of PLS patients. Monitoring CatC in the urine could be utilized as an early, simple, reliable, low cost diagnostic technique for PLS.